Antibioterapia natural in vitro contra procesos bacterianos gastrointestinales de cuyes (Cavia porcellus linnaneus) - Castro Mayorga, Alejandra Maria (2022)
Gastrointestinal diseases are a very common presentation topic in guinea pig farming however, it is important to evaluate the dynamics of bacterial infections over a period of time. The present research work took place at the "La María" Campus of the State Technical University of Quevedo